1989
DOI: 10.1093/nar/17.22.9113
|View full text |Cite
|
Sign up to set email alerts
|

H2A.X. a histone isoprotein with a conserved C-terminal sequence, is encoded by a novel mRNA with both DNA replication type and polyA 3′ processing signals

Abstract: A full length cDNA clone that directs the in vitro synthesis of human histone H2A isoprotein H2A.X has been isolated and sequenced. H2A.X contains 142 amino acid residues, 13 more than human H2A.1. The sequence of the first 120 residues of H2A.X is almost identical to that of human H2A.1. The sequence of the carboxy-terminal 22 residues of H2A.X is unrelated to any known sequence in vertebrate histone H2A; however, it contains a sequence homologous with those of several lower eukaryotes. This homology centers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
102
0
3

Year Published

1992
1992
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 154 publications
(113 citation statements)
references
References 62 publications
(56 reference statements)
7
102
0
3
Order By: Relevance
“…First identified in 1980 in human cells as an electrophoretic isoform of the core histone H2A [2], H2AX was subsequently sequenced in the late 80's [3]. These early studies noted the presence of a short COOH terminal tail not found in any other mammalian H2A isoforms, but being present-with various degrees of homology and linker lengths-in the unique H2A homologue of lower eukaryotes [3,4].…”
Section: Introduction: the Tale Of A Tailmentioning
confidence: 99%
See 1 more Smart Citation
“…First identified in 1980 in human cells as an electrophoretic isoform of the core histone H2A [2], H2AX was subsequently sequenced in the late 80's [3]. These early studies noted the presence of a short COOH terminal tail not found in any other mammalian H2A isoforms, but being present-with various degrees of homology and linker lengths-in the unique H2A homologue of lower eukaryotes [3,4].…”
Section: Introduction: the Tale Of A Tailmentioning
confidence: 99%
“…These early studies noted the presence of a short COOH terminal tail not found in any other mammalian H2A isoforms, but being present-with various degrees of homology and linker lengths-in the unique H2A homologue of lower eukaryotes [3,4]. H2AX constitutes a major H2A species, and its levels vary from 2-25% of the mammalian histone H2A pool depending on the cell line or tissue examined [5,6].…”
Section: Introduction: the Tale Of A Tailmentioning
confidence: 99%
“…More-sensitive assays are being developed, an important one being the ability to detect the cellular presence of the most serious and potentially lethal type of cellular damage, the DNA doublestrand break (DSB). This assay is based on the finding that one of the highly conserved histone proteins that package the DNA into chromatin, H2AX, becomes phosphorylated at the sites of nascent DNA DSBs (5)(6)(7)(8). The response is highly amplified and rapid, involving the phosphorylation of hundreds to thousands of H2AX molecules within minutes on several megabase equivalents of chromatin flanking the DSB.…”
mentioning
confidence: 99%
“…In some cases, such mRNAs represent a very minor part of the total mRNA pool (Levine et al, 1987). In several histone H I transcripts in chicken (Kirsh et al, 1989) and mouse (Cheng et al, 1989), as well as in transcripts encoding the histone H2A.X variant (Mannironi et al, 1989;Nagata et al, 1991), the two modes of the 3' processing occur with comparable efficiency in the same cell or tissue type. In all these cases the polyadenylated messengers behave as replacement type histone mRNAs, which are not destabilized at the end of the S-phase, in contrast to the nonpolyadenylated mRNAs.…”
mentioning
confidence: 99%
“…In all these cases the polyadenylated messengers behave as replacement type histone mRNAs, which are not destabilized at the end of the S-phase, in contrast to the nonpolyadenylated mRNAs. The existence of such poly(A)-containing mRNAs is probably necessary to ensure the basal synthesis of the respective histone variants (Kirsh et al, 1989;Cheng et al, 1989;Mannironi et al, 1989;Nagata et al, 1991).…”
mentioning
confidence: 99%